Estudio de prefactibilidad para la implementación de una planta procesadora de fermentado de yacón (Smallanthus sonchifolius) - Laverian Roldan, Adrian Kenny (2023)
During a period of eight months, a study was carried out for the installation of a yacon fermentation plant in returnable containers. This alcoholic beverage is intended to be a healthy option for those consumers who present symptoms of diabetes and wish to choose to drink a natural liquor, using yacon as raw material, characteristic of the Andean areas that contributes to lowering blood glucose levels, improves the immune system and prevents the early stages of colon cancer. The target market will be those people between the ages of 18 and 55, belonging to socioeconomic levels B and C of Metropolitan Lima. The presentation of the product will be in 750-milliliter bottles at a price of S/ 53.8. Through the market study it was determined that the demand of the project for the years 2022 and 2027 are 42,742 and 46,515 bottles, respectively. The factor ranking techniques were applied in Macrolocation as well as in Microlocation and Huachipa, Lurigancho of Metropolitan Lima was chosen as the strategic location to install the production plant with a total area of 785.32 m2. In addition, in chapter four the market relations, equilibrium point, productive resources and technology were calculated, these last two data were found by the material balance and plant capacity of chapter five, it is worth mentioning that the bottleneck found has an annual yield of 55,364 liters and the number of operators are 4 people as well as indirect labor that are four people, in addition to the seventeen machines described in this document. For the structure of the organization of the company, it is made up of the General Manager - Main responsible administrator and two heads of areas: Marketing, sales and Production and quality. Finally, the project will have an investment of S/ 1 260 822,60, 40% of which is financed by the BBVA bank at an effective annual rate of 21,48 % and with its own contribution amounting to S/ 756 493,56, generating a positive economic and financial VAN and TIR, the project being viable.